ANALISIS PERKUATAN LERENG AKIBAT LONGSOR DI DESA DOMPYONG - Endah Nurhidayah; Paksitya Purnama Putra; Indra Nurtjahjaningtyas (Rekayasa Sipil, 2022)
An unstable slope is identical to the low value of their factor of safety (FS). Slope with low FS are in critical condition, which can cause landslides. On the other hand, the presence of triggering factor such as rain and human activities will increase the percentage of landslide. It has happened in Dompyong village. The Rocscience Slide Program, used to analyze slope stability in Dompyong village based on the simplified – bishop method. Based on the analysis, the FS value of the initial condition of slope is 0,85. Therefore, the slope is in critical condition because the FS value is less than 1,07. A combination method of retaining wall and micropiles is used to strengthen slope stability. This method can increase the FS value to 1,370. The slope is in a stable condition relatively because the FS value is more than 1,25.